Short-term effects of high-intensity laser therapy on frozen shoulder: A prospective randomized control study. Issue 6 (December 2015) - Kim, Sae Hoon; Kim, Yeon Ho; Lee, Hwa-Ryeong; Choi, Young Eun
Abstract: Background: Frozen shoulder, which is characterized by shoulder pain and limitation of the range of motion (ROM), is a common disorder. High-intensity laser therapy (HILT) was recently introduced in the musculoskeletal therapeutic field. Objective: The objective of this study is to evaluate the clinical efficacy of HILT in patients with frozen shoulder. Design: A prospective randomized controlled study. Method: Patients with frozen shoulder were randomly divided into 2 groups: a HILT group ( n = 33) and a placebo group ( n = 33). The treatment was administered 3 times per week on alternate days for 3 weeks. For all patients, the visual analog scale (VAS) for pain, VAS for satisfaction, and passive ROM were measured at baseline and 3, 8, and 12 weeks after the treatment. Results: The HILT group had a lower pain VAS score at 3 weeks (3.2 ± 1.7 vs. 4.3 ± 2.2, p = 0.033) and 8 weeks (2.2 ± 2.0 vs. 3.4 ± 2.7, p = 0.042), however, no statistically significant difference in the pain VAS was observed between the two groups at the final follow-up (12 weeks). No statistical difference in the ROM and the satisfaction VAS was observed between the 2 groups at serial follow-ups. Conclusions: In management of frozen shoulder, HILT provided significant pain relief at 3 and 8 weeks, but not at the final follow-up time point. HILT is a noninvasive adjuvant treatment that can reduce pain in frozen shoulders. Further study is needed in order to optimize the dose and duration of HILT. Highlights: Frozen shoulder is a common disorder in the shoulder. High-intensity laser therapy (HILT) is recently introduced in musculoskeletal therapeutic field. HILT treated group had lower pain visual analog scale compared to placebo group. Adjuvant HILT can reduce pain in frozen shoulders in early treatment period.